Объяснение:
( x + 2 ) ^ 4 - 4 * ( x + 2 ) ^ 2 - 5 = 0 ;
Пусть ( х + 2 ) ^ 2 = а, тогда:
а ^ 2 - 4 * a - 5 = 0 ;
a1 = ( 4 - √36 ) / ( 2 * 1 ) = ( 4 - 6 ) / 2 = - 2 / 2 = - 1 ;
a2 = ( 4 + √36 ) / ( 2 * 1 ) = ( 4 + 6 ) / 2 = 10 / 2 = 5 ;
Тогда:
1 ) ( x + 2 ) ^ 2 = - 1 ;
x ^ 2 + 4 * x + 4 = - 1 ;
x ^ 2 + 4 * x + 4 + 1 = 0 ;
x ^ 2 + 4 * x + 5 = 0 ;
Нет корней ;
2 ) ( x + 2 ) ^ 2 = 5 ;
x ^ 2 + 4 * x + 4 = 5 ;
x ^ 2 + 4 * x - 1 = 0 ;
x1 = ( -4 - √20 ) / ( 2·1 ) = -2 - √5 ;
x2 = ( -4 + √20 ) / ( 2·1 ) = -2 + √5 ;
ответ: х = -2 - √5 и х = -2 + √5
x^3+4x^2-4x-16=0
x^2(x+4)-4(x+4)=0
(x+4)(x^2-4)=0
(x+4)(x-2)(x+2)=0
x1=-4
x2=2
x3=-2